Inverse high internal phase emulsion polymerization (i-HIPE) of GMMA, HEMA and GDMA for the preparation of superporous hydrogels as a tissue engineering scaffold - Nalawade, Archana C.; Ghorpade, Ravindra V.; Shadbar, Sadiqua; Qureshi, Mohammed Shadbar; Chavan, Nayaku; Khan, Ayesha A.; Ponrathnam, S. (Journal of Materials Chemistry B, 2016)
A series of novel superporous hydrogels for regenerative medicine were prepared by oil-in-water (o/w) or inverse high internal phase emulsion (i-HIPE) copolymerization of glycerol monomethacrylate (GMMA), 2-hydroxy ethyl methacrylate (HEMA) and glycerol dimethacrylate (GDMA) as a cross-linker using a non toxic solvent and a redox initiator system at the physiological temperature (37 degrees C). The monomer GMMA was synthesized from glycidyl methacrylate (GMA) by an alternative facile method using Amberlyst-15. The described i-HIPEs showed a significantly wider stability window. The polyHIPE hydrogels were characterized by FTIR, BET method for surface area, mercury porosimetry, SEM, DSC, TGA, XRD, compressive strain and strain recovery. The swelling ratio of the hydrogels and their degradation in 0.007 M NaOH and lipase B (Candida antarctica) solutions were determined gravimetrically and the rate of degradation was explained in terms of the molecular structure of the hydrogels. The morphological studies showed that the pore diameter varied between 20 and 30 mu m and the pore throats (interconnecting windows) diameter was in the range of 4-8 mu m. The described polyHIPE hydrogels were found to have an open cell morphology and interconnected pore architecture, which are important characteristics for scaffold applications. The initial cytotoxicity study performed according to ISO-10993-5 indicated cytocompatibility (97% cell viability) and the subsequent cell seeding and proliferation study exhibited 55-88% cell viability (increased monotonously from GHG-1 to GHG-5), which could be attributed to modulation of the physical and chemical properties of the hydrogels. The described super porous hydrogels are considered as potential candidates for scaffold materials in tissue engineering applications.